Delay Sensitive Energy Management Clusterhead Routing Protocol for Securing Underwater Acoustic Sensor Networks - Sahana, S; Vinothini, V (International Journal of Computer Sciences and Engineering, 2025)
Underwater sensor network consists of number of various sensors and autonomous underwater vehicles deployed underwater to coordinate, interact and share information among them to carry out sensing and monitoring functions. Underwater environment differs from terrestrial radio environment both in terms of energy costs and channel propagation phenomena. The goal of the project is to reduce the occurrence of delays and attacks, during data transmission among sensor nodes in under water acoustic sensor network by introducing a protocol called delay sensitive energy management cluster head routing protocol in order to enhance the energy efficiency of the sensor network